ARCHAEOLOGY IN THE SHADOW OF THE ZIGGURAT INITIAL RESULTS OF A COLLABORATIVE PROGRAMME AT UR - Al-Hamdani, Abdulameer; Ven, Annelies Van de (2022)
The region of ancient Mesopotamia has long been a focal point for archaeological investigations. Since the early explorations of the nineteenth century, the discipline has been transformed along with the region, witnessing colonialism and independence, as well as coups and conflicts. At the end of the twentieth century, international archaeological investment experienced a significant decline in this region, due to ongoing war and embargoes. In the wake of the Iraq War, foreign archaeological teams have begun flooding back into the Kurdistan Region of Iraq and the southern governorates. However, the approach to excavations has changed a great deal since the fall of the Ba'ath government. Where once there was a strict policy of segregation between foreign and local archaeologists, collaborations are now encouraged. The difficulty now has become finding how to build and sustain these relationships, re-opening lines of exchange and learning. This article approaches this question with the case study of the 2017 excavations at Ur in the Dhi Qar governorate in the south of Iraq
لطالما كانت منطقة بلاد ما بين النهرين القديمة نقطة محورية للتنقيب عن الآثار والبحوث الأثرية، ومنذ الاستكشافات المبكرة في القرن التاسع عشر، واكب التغيير في أساليب البحث والتنقيب التغيرات التي مرت بها هذه المنطقة ، حيث شهدت الاستعمار وثم الاستقلال ، فضلاً عن الانقلابات والصراعات . في نهاية القرن العشرين، كان هناك انخفاظ ملحوظ في حجم الاستثمار الدولي في مجال علم الآثار في هذه المنطقة ، وذلك بسبب الحروب المستمرة وعمليات الحظر والعقوبات . وفي أعقاب حرب العراق ، بدأت فرق الآثار الأجنبية تتدفق عائدة إلى إقليم كردستان العراق والمحافظات الجنوبية . غير أن المنهج الأركيولوجي تغير كثيرا منذ سقوط حكومة حزب البعث العربي الاشتراكي . حيث في السابق كانت هناك سياسة للفصل بين علماء الآثار المحليين و الأجانب وكانت سائدة و صارمة، وأما الآن أصبح التعاون بينهم مشجعاً . ومن التحديات الآن، كيفية إيجاد تعاون فعال وبناء شراكات تعيد الحوار وتبادل المعرفة . تتناول هذه المقالة هذا السؤال مع دراسة الحالة الخاصة بعمليات الحفر والتنقيب عن الآثار عام 2017 في أور بمحافظة ذي قار في جنوب العراق .